Analysis and Design of E-Commerce Based Sales Information At Pt Bahtera Ekatama Sejahtera With User Centered Design Method - Samuel Samuel (Komunitas Dosen Indonesia, 2021)
In this increasingly difficult economic situation, there is a lot of competition in various fields of life, including competition in the business world. Many companies are competing to get a market, so this spur stores to try to keep moving forward in improving their business. In addition, with the advancement of technology, companies are required to keep up with the times so as not to be left behind by others. For the company to grow and develop properly, the company must be able to anticipate increasingly competitive economic developments by carrying out the right strategy so as not to be left out in the competition. E-Commerce is a dynamic set of technologies, applications, and business processes that connect companies, consumers, and specific communities through electronic transactions and electronic trading of goods, services, and information. Almost all agencies use the internet and have a website for the smooth running of their business. So far, the company does not have a website that can display the products sold by the store so that consumers are less familiar and product sales are less than optimal. User Centered Design (UCD) is a design philosophy that places the user at the center of the system development process. The UCD approach has been supported by various techniques, methods, tools, procedures, and processes that help design interactive systems that are more user-centric